Ectopic Supernumerary Tooth Displacement into Nasal Cavity: Rare Presentation in Cleft Lip and Palate-Case Report and Literature Review. - Cerantula, Camila [UNESP]; Guimarães, Ângela Maira; Pulino, Bianca; Guerra, Raphael Capelli; Garcia Júnior, Idelmo Rangel [UNESP]; Scariot, Rafaela (SAGE Publications, 2025)
Objective To describe a rare complication of supernumerary tooth displacement into the nasal cavity and subsequent migration to the gastrointestinal tract in a patient with cleft lip and palate. Design Case report and literature review.SettingHospital-based care at the Center for Comprehensive Care of Cleft Lip and Palate patients. Patients, ParticipantsA 10-year-old male with a unilateral complete cleft lip and palate presenting 2 impacted supernumerary teeth along the cleft line.InterventionsSurgical extraction of both supernumerary teeth was planned. During the procedure, 1 tooth was inadvertently displaced into the nasal cavity. Serial imaging was used to monitor its location and progression.Main outcome MeasuresAssessment of the displaced tooth's trajectory and clinical outcomes through radiographic follow-up.ResultsThe displaced tooth migrated from the nasal cavity to the gastrointestinal tract, as confirmed by sequential radiographs. The patient remained asymptomatic throughout and experienced spontaneous elimination of the tooth without complications. Conclusions This case highlights the increased risk of tooth displacement during extraction in patients with cleft lip and palate due to compromised anatomical support, and although multidisciplinary perioperative management was essential, the migration of the tooth into the gastrointestinal tract demonstrates that even with careful planning rare adverse events may still occur, reinforcing the value of multidisciplinary case conferences for a consistent treatment plan, as well as preventive strategies such as coordination with otorhinolaryngology, intraoperative nasal endoscopy in high-risk cases, securing the tooth during manipulation and applying gentle traction to minimize the likelihood of such events.